Photothermally Triggered Copper Payload Release for Cuproptosis‐Promoted Cancer Synergistic Therapy - Zhou, Jie; Yu, Qiao; Song, Juan; Li, Shan; Li, Xiang‐Ling; Kang, Bin K.; Chen, Hong‐Yuan; Xu, Jing‐Juan (Angewandte Chemie International Edition, 2023)
Cuproptosis is a new form of programmed cell death and exhibits enormous potential in cancer treatment. However, reducing the undesirable Cu ion release in normal tissue and maximizing the copper‐induced therapeutic effect in cancer sites are two main challenges. In this study, we constructed a photothermally triggered nanoplatform (Au@MSN‐Cu/PEG/DSF) to realize on‐demand delivery for synergistic therapy. The released disulfiram (DSF) chelated with Cu2+ in situ to generate highly cytotoxic bis(diethyldithiocarbamate)copper (CuET), causing cell apoptosis, and the formed Cu+ species promoted toxic mitochondrial protein aggregation, leading to cell cuproptosis. Synergistic with photothermal therapy, Au@MSN‐Cu/PEG/DSF could effectively kill tumor cells and inhibit tumor growth (inhibition rate up to 80.1 %). These results provide a promising perspective for potential cancer treatment based on cuproptosis, and may also inspire the design of advanced nano‐therapeutic platforms. A gold‐nanorod‐based, copper‐doped, and disulfiram (DSF)‐loaded multifunctional therapeutic nanoplatform (Au@MSN‐Cu/PEG/DSF) was fabricated to deliver DSF and Cu2+ into cancer cells efficiently. A photothermal effect triggered on‐command payload release remotely to form cytotoxic bis(diethyldithiocarbamate)copper (CuET) and Cu+ in situ. This cuproptosis‐based strategy offers synergistic therapeutic modalities.